2019
DOI: 10.1007/978-3-030-11015-4_38
|View full text |Cite
|
Sign up to set email alerts
|

CapsuleGAN: Generative Adversarial Capsule Network

Abstract: We present Generative Adversarial Capsule Network (Cap-suleGAN), a framework that uses capsule networks (CapsNets) instead of the standard convolutional neural networks (CNNs) as discriminators within the generative adversarial network (GAN) setting, while modeling image data. We provide guidelines for designing CapsNet discriminators and the updated GAN objective function, which incorporates the CapsNet margin loss, for training CapsuleGAN models. We show that CapsuleGAN outperforms convolutional-GAN at model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(77 citation statements)
references
References 9 publications
0
76
0
1
Order By: Relevance
“…Dilin et al [23] solves the dynamic routing as an optimization problem, and achieves better performance by introducing KL divergence between the coupling distribution. CapsGan [11] uses a capsule network as the discriminator in the GAN pipeline, to get visually better results than convolutional GANs. In contrast to these, our work focuses on going deeper with the capsule networks and increase its performance on more complex datasets.…”
Section: Related Workmentioning
confidence: 99%
“…Dilin et al [23] solves the dynamic routing as an optimization problem, and achieves better performance by introducing KL divergence between the coupling distribution. CapsGan [11] uses a capsule network as the discriminator in the GAN pipeline, to get visually better results than convolutional GANs. In contrast to these, our work focuses on going deeper with the capsule networks and increase its performance on more complex datasets.…”
Section: Related Workmentioning
confidence: 99%
“…In another domain, Iesmantas and Alzbutas applied a capsule network based on binary classification to breast cancer detection [69]. Jaiswal et al reported a capsule-based GAN [70]. Yang et al applied a capsule network to the text domain [71].…”
Section: Capsule Networkmentioning
confidence: 99%
“…ations than a typical CNN thanks to using a vector output instead of a scalar one, and by replacing the max-pooling operation with a dynamic routing algorithm. Although Capsules have some advantages over CNNs, as demonstrated by the encouraging results on 2D image classification [18,7] and segmentation [10], there is currently no work proposed based on the Capsule Network for 3D object classification. Therefore, in this paper, we propose an extension of Capsule Networks such that it becomes applicable to 3D point cloud data, and investigate the utility for the purpose of 3D object classification.…”
Section: Related Workmentioning
confidence: 99%